Gyromitra persicula sp. nov. (Discinaceae, Pezizales), a novel discoid Gyromitra from Northwestern North America - Dirks, Alden C.; Beug, Michael W.; Methven, Andrew S.; Miller, Andrew N.; James, Timothy Y. (Phytotaxa, 2024)
Gyromitra persicula (Discinaceae, Pezizales), a new species from Washington state, USA, is described. Like its sister species G. leucoxantha, G. persicula has reticulate ascospores with blunt apiculi that form concave depressions resembling a fishtail. Gyromitra persicula is differentiated from G. leucoxantha by its smaller size, peach to buff coloration, and nrDNA ITS. Further collections are required to better understand the distribution and abundance of this discoid Gyromitra, which is currently only known from a small geographic area of temperate rainforest.